1999
DOI: 10.1001/archopht.117.11.1479
|View full text |Cite
|
Sign up to set email alerts
|

Screening for Glaucoma With Frequency-Doubling Technology and Damato Campimetry

Abstract: To assess frequency-doubling technology (FDT) perimetry (Humphrey Systems, San Leandro, Calif) and Damato campimetry (Precision Vision, Villa Park, Ill) for detecting glaucoma in a public glaucoma screening. Methods: A 2-day public glaucoma screening was held at 2 different institutions. Each subject underwent 2 visual field screening tests (Damato campimetry and FDT perimetry in screening mode), an ophthalmologic examination, and Humphrey perimetry (24-2 FASTPAC) for each eye. Eyes were divided into 4 categor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
52
1
3

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 19 publications
1
52
1
3
Order By: Relevance
“…[24][25][26][27][28][29][30] Three studies investigated OKP as a screening device, and reported similar results with sensitivities from 35 to 92% and specificities from 90 to 96%. [31][32][33] The concept of using a quick visual field test as a screening tool for glaucomatous defects is not new. Several studies have investigated the role of frequencydoubling technology (FDT) as a screening tool for glaucoma.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[24][25][26][27][28][29][30] Three studies investigated OKP as a screening device, and reported similar results with sensitivities from 35 to 92% and specificities from 90 to 96%. [31][32][33] The concept of using a quick visual field test as a screening tool for glaucomatous defects is not new. Several studies have investigated the role of frequencydoubling technology (FDT) as a screening tool for glaucoma.…”
Section: Discussionmentioning
confidence: 99%
“…10,11 The studies revealed wide variation of FDT performance and the reported sensitivity and specificity ranged between 19 and 99%, and 57 and 87%, respectively. [33][34][35][36][37] The novelty of DMCO compared with the previous evaluations of possible visual field tests is simply related to its free accessibility. However, continuous improvement of the website is important and necessary to implement DMCO as a diagnostic tool.…”
Section: Discussionmentioning
confidence: 99%
“…Vários tipos de campímetro foram utilizados com resultados variáveis, porém, em geral mais satisfatórios do que aqueles encontrados com o uso da medida de PO, com especificidade variando entre 91 e 95% e sensibilidade entre 52 e 94%. A sensibilidade varia com o estágio de evolução da doença, chegando de 86 a 96% em casos de glaucoma moderado e a 100% nos casos severos (9)(10)(11)(12)(13) . Apesar do desempenho deste tipo de exame ser mais satisfatório, ele demanda tempo (3 a 12 min/olho), correção para perto e um técnico treinado para a realização do mesmo.…”
Section: Eficácia Da Associação De Métodos Diagnósticos No Rastreamenunclassified
“…De qualquer forma, sugere-se que o comprometimento de células específicas (como as My), que estão distribuídas difusamente na superfície retiniana, poderia diminuir o fenômeno de redundância, impedindo que a disfunção de um grupo específico de células possa ser mascarada por células vizinhas (10)(11)(12)(13) . Essa modalidade perimétrica tem-se mostrado altamente promissora para utilização em triagens populacionais (14) .…”
Section: Descritoresunclassified
“…Já se demonstrou que essa tecnologia é altamente promissora para triagens populacionais (8,10,14), mas sua aplicação na clínica ainda tem sido objeto de estudo (13,15) . O conhecimento das flutuações que podem ocorrer em novos tipos de perimetria é de grande importância, tanto em condições normais quanto em situações em que já existe comprometimento do campo visual.…”
Section: I S C U S S ã Ounclassified